Bicara siswa [videorecording] : interview with Y. Bhg. Datuk Prof. Ir. Dr. Mohd. Zulkifli bin Tan Sri Mohd. Ghazali, UTM Vice-Chancellor - 495834 Universiti Teknologi Malaysia; Mohd. Zulkifli Mohd. Ghazali, Tan Sri Prof. Ir. Dr., 1951- (2002)
44